Relativizer 'illi' in Arabic Dialects - Galal, Mohamed (Kansas Working Papers in Linguistics, 2004)
According to the grammars of Arabic dialects illi only occurs following a definite head noun. However, based on fresh data from Brustad (2000), the relative marker illi is also found to occur following an indefinite head noun in Egyptian, Moroccan, Syrian, and Kuwaiti Arabic. Brustad (2000) accounts for this new occurrence via the semantics of individuation; her solution seems to be relatively problematic and sometimes ad-hoc. Basically, I claim that a solution based on the hierarchy of individuation does not work. I further propose there are two phonologically identical but syntactically different Mi's: the first one generates for definiteness, and the other is only created by overgeneralized analogy.